The Influence Of Leadership Style And Work Motivation On Employee Performance (Survey on Margabakti Village Apparatuses Cibeureum Tasikmalaya) - Alwa Assaigof; H. Ari Arisman; Suci Putri Lestari (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
This research was conducted with the aim of knowing the effect of leadership style and work motivation on employee performance in Margabakti Village Apparatuses Cibeureum District Tasikmalaya City. The method used in this study was a survey method using data obtained directly through questionnaires that were distributed to 63 respondents who were Margabakti Village Apparatuses Cibeureum District Tasikmalaya City. The technique used in this research is multiple regression analysis. Based on the research results, it is known that Leadership Style and Work Motivation simultaneously have a significant effect on the Performance of Employees in the Margabakti Village Cibeureum District Tasikmalaya City. Leadership style partially has a significant effect on the performance of Margabakti Sub-district Employees Cibeureum District Tasikmalaya City. Partially, work motivation has a significant effect on the performance of Margabakti Village Employees Cibeureum District Tasikmalaya City.